Saphenous vein bypass for direct coronary revascularization. Issue 1 (January 1972) - Ross, D. N.; Gonzalez-Lavin, L.; Frazier, T.
Abstract : The surgical approach to myocardial revascularization has been undertaken on the same basis as in peripheral vascular surgery. Aorta to coronary saphenous vein bypass has been found to be one of the best methods of providing immediate augmentation of coronary blood flow. Thirty-eight patients have been operated upon. The hospital mortality was 5.3% and the total mortality has been 13.2% in a follow-up extending one month to two years. Among the survivors, 90% had excellent initial results with complete disappearance of symptoms and marked improvement in exercise tolerance. The authors advocate the saphenous vein bypass as the procedure of choice for elective coronary revascularization.